NanoBRET: The Bright Future of Proximity-Based Assays - Dale, Natasha C.; Johnstone, Elizabeth K. M.; White, Carl W.; Pfleger, Kevin D. G. (Frontiers in Bioengineering and Biotechnology, 2019)
Bioluminescence resonance energy transfer (BRET) is a biophysical technique used to monitor proximity within live cells. BRET exploits the naturally occurring phenomenon of dipole-dipole energy transfer from a donor enzyme (luciferase) to an acceptor fluorophore following enzyme-mediated oxidation of a substrate. This results in production of a quantifiable signal that denotes proximity between proteins and/or molecules tagged with complementary luciferase and fluorophore partners. BRET assays have been used to observe an array of biological functions including ligand binding, intracellular signalling, receptor-receptor proximity and receptor trafficking, however, BRET assays can theoretically be used to monitor the proximity of any protein or molecule for which appropriate fusion constructs and/or fluorophore conjugates can be produced. Over the years, new luciferases and approaches have been developed that have increased the potential applications for BRET assays. In particular, the development of the small, bright and stable Nanoluciferase (NanoLuc; Nluc) and its use in NanoBRET has vastly broadened the potential applications of BRET assays. These advances have exciting potential to produce new experimental methods to monitor protein-protein interactions (PPIs), protein-ligand interactions and/or molecular proximity. In addition to NanoBRET, Nluc has also been exploited to produce NanoBiT technology, which further broadens the scope of BRET to monitor biological function when NanoBiT is combined with an acceptor. BRET has proved to be a powerful tool for monitoring proximity and interaction, and these recent advances further strengthen its utility for a range of applications.